An experimental course in mathematics for the ninth year. units 10 and 11, open sentences in two variables and relations and functions - New York State Education Dept., Albany; New York State Education Dept., Albany ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1965)
This teaching guide is the fourth of five experimental editions containing materials and methods for teaching a revised mathematics program in grade 9. Background material for teachers as well as questions and activities for classroom presentations are provided in the content areas of (1) open sentences in two variables (unit 10) and (2) relations and functions (unit 11). Unit 10 includes sections on algebraic solutions, solution by graphing, and solution of inequalities. Unit 11 includes sections on relations, functions (algebraic and trigonometric), range and domain, graphing relations and functions, and slope and intercept. (rp)
Educational level discussed: Grade 9.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Algebra; Curriculum; Curriculum Guides; Grade 9.; Mathematics; Secondary School Mathematics; Teaching Guides; Trigonometry; New York